JENIS LEUKOSIT MENCIT (Mus musculus) PASCA STRES AKUT DENGAN PERLAKUAN EKSTRAK ETANOL BIJI PALA (Myristica fragrans Houtt) - Zulhaimi Hendrajid; Yuniasih M. J. Taihuttu; Parningotan Y. Silalahi; Laura B. S. Huwae; Vina Z. Latuconsina (PAMERI, 2020)
Glucocorticoid represent a kind of stress hormone that suppressed the normal immune response by blockade T-Helper 1 cell program that has function to produce gamma interferon. Glucocorticoid could give some impact like losing weight, immunodeficiency, and change the differentiation of leukocyte. This fruit of nutmeg (Myristica fragrans Houtt) is a traditional plant in Maluku and contains secondary metabolite compounds that can induce the secretion of immune system (immunomodulatory). This research has a target to discover the number of mice leukocyte and its various cell that will be induced by stress itself and will be given ethanol extract of nutmeg seed. This research considers as pure experimental with posttest only control group design. 30 mice divided into 5 different groups, which are normal control (KN), negative control (stress), positive control (stress+0.2 Alprazolam), ethanol extract of nutmeg seed 4% (P1) and 16% (P2). Group control of K-, K+, P1, P2 were stress inducted using FST method for 6 minutes, and then give orally all the treatment for 7 days long and at the 8th days the blood collected intracardially. The counting process held as manual observation. The data analyzed by using ANOVA. The result of this research shows that P1 on the experiment could decrease the presentation of neutrophil, increase the presentation of monocyte and lymphocyte, meanwhile on P2 could decrease the presentation of neutrophil and monocyte, increase the presentation of lymphocyte and has no effect to the percentation of eosinophil and basophil. We can conclude that the giving of ethanol extract of nutmeg seed didn’t give a specific effect to the average mount of neutrophil, monocyte, lymphocyte, eosinophil, and basophil (p>0.05).